Pesnjenje v vojaški suknji in proti njej 1515-1918 Monografija z antologijo vojaških pesmi - Stanonik, Marija (ZRC SAZU, Založba ZRC, 2020)
The historical timeframe of the present monograph ('Five Centuries of Writing Poetry in a Military Uniform and Against it 1515-1918')begins at around 1500, the period in which most of the Slovenian ethnic territory was taken over by the Habsburgs and ends with the defeat of Austro-Hungary during the First World War between 1914-1918. This stretch of time is particularly marked by the first printed lines of the Slovenian rebel poem written during the pan-Slovenian peasant uprising of 1515, which is even older than Trubar's Abecedary and Catechism (1550), and the poem depicting the tragic Judenburg mutiny of 1917 for which the leader of the revolt, Anton Hafner, paid with his life.